Pemberdayaan Siswa sebagai Agen Perubahan: Model Dukungan Sebaya dalam Mencegah Perundungan di Sekolah Dasar: Empowering Students as Change Agents: Peer Support Model in Preventing Bullying in Elementary School - Kurniawati, Yunita; Hasanah, Nur (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Mental health is an important aspect of individual well-being, especially in the school environment. Good mental health can enhance psychological well-being, quality of life, and individual health, and also support students' academic performance. However, one issue that often arises is bullying. Both victims and perpetrators can suffer from bullying. Peer support plays a key role in preventing bullying in schools. Peers can be a source of emotional support for bullying victims, build positive relationships with all students at school, practice positive attitudes, thus becoming role models for other students, and raise awareness about the impact of bullying. The bullying prevention program involved 76 elementary school students from grades 4 to 6 in Malang Regency. The activities consist of three stages. The preparation stage involves conducting an assessment to identify the analysis. The psychoeducation is adapted to the student's development stage. The results show an increase in understanding of the role of peer support in bullying prevention.